Assessment of the Depth of the Deformed Layer in the Roller Burnishing Process - Kowalik, M.; Mazur, T.; Trzepiecinski, T. (Проблемы прочности, 2018)
This paper presents the methods used to determine the depth of the plastically deformed top layer in the roller burnishing process. An analytical method was developed for determining the depth of the plastically deformed layer on the basis of the Hertz–Bielayev theory. The depth of deformation was obtained as a function of the process parameters: burnishing force, material strength and roller radius. The analytical solution has been verified using an original method based on the measurement of the face profile of rings. A mathematical model for a theoretical solution and a plan for experimental tests have been developed. The numerical simulation of the depth of the plastically deformed layer was carried out based on the finite element method. The results of deformation depth as a function of roller force, material strength and roller geometry show a good agreement between analytical and experimental methods.